Keep calm and transcribe on: chromatin changes with age, but transcription can learn to live with it - Cian J Lynch; Manuel Serrano (Molecular Systems Biology)
Abstract Assessing age‐related tissue dysfunction represents an emerging field and involves analyses that are far from trivial, often requiring the integration of several large‐scale (“omic”) techniques. In their recent work, Tessarz and colleagues (Bozukova et al, 2022) characterize changes in the transcriptional machinery during aging in mice and report some surprising findings.